Neurochemical and behavioral profiling of the selective GlyT1 inhibitors ALX5407 and LY2365109 indicate a preferential action in caudal vs. cortical brain areas - Perry, Kenneth W.; Falcone, Julie F.; Fell, Matthew J.; Ryder, John W.; Yu, Hong; Love, Patrick L.; Katner, Jason; Gordon, Kimberly D.; Wade, Mark R.; Man, Teresa; Nomikos, George G.; Phebus, Lee A.; et al. (Neuropharmacology, 2008)
Selective inhibitors of the glycine transporter 1 (GlyT1) have been implicated in central nervous system disorders related to hypoglutamatergic function such as schizophrenia. The selective GlyT1 inhibitors ALX5407 (NFPS) and LY2365109 {[2-(4-benzo[1,3]dioxol-5-yl-2- tert-butylphenoxy)ethyl]-methylamino}-acetic acid increased cerebrospinal fluid levels of glycine and potentiated NMDA-induced increases in dialysate levels of neurotransmitters in the prefrontal cortex (PFC) and the striatum. However, higher doses produced both stimulatory and inhibitory effects on motor performance and impaired respiration, suggesting significant involvement of cerebellar and brain stem areas. A dual probe microdialysis study showed that ALX5407 transiently elevated extracellular levels of glycine in the PFC with more sustained increases in the cerebellum. In support of these findings, immuno-staining with pan-GlyT1 and GlyT1a antibodies showed a higher abundance of immunoreactivity in the brain stem/cerebellum as compared to the frontal cortical/hippocampal brain areas in four different species studied, including the mouse, rat, monkey and human. In addition, the inhibitory effects of ALX5407 on cerebellar levels of cGMP in the mouse could be reversed by the glycine A receptor antagonist strychnine but not the glycine B receptor antagonist L-701324. We propose that the adverse events seen with higher doses of ALX5407 and LY2365109 are the result of high GlyT1 inhibitory activity in caudal areas of the brain with sustained elevations of extracellular glycine. High levels of glycine in these brain areas may result in activation of strychnine-sensitive glycine A receptors that are inhibitory on both motor activity and critical brain stem functions such as respiration.